PEMBUATAN WEBSITE BAHAN BELAJAR TRANSORMASI GEOMETRI - Nicko Sebastian; Dyah Erni Herwindiati; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Developing a website to be used as a medium of learning mathematics. The material presented on the website discusses transformation geometry which includes translation, rotation, and dilation. In the process of making this website, it will be explained how the stages of development and how users respond to the website. The development process is carried out starting with (1) needs analysis (2) media design (3) expert validation (4) media testing (5) until new products are created in the form of learning media. The expert validation stage is carried out by lecturers and mathematics teachers. The questionnaire analysis is carried out in a descriptive qualitative manner using form filling.